Systematic trends in the spin-orbit splitting toward weak-binding - Chen, Jie (Frontiers in Physics, 2025)
Spin–orbital (SO) splitting in atomic nuclei results from the coupling between a nucleon’s spin and its orbital angular momentum, fundamentally influencing nuclear structure, especially near the magic numbers. This paper reviews the impact of various effects on SO-splitting, including tensor and weak-binding effects in neutron-rich and weakly bound nuclei, focusing on both theoretical interpretations and recent experimental results. The study summarizes new experimental results on SO-splitting in isotopes such as 34Si, 32Si, and 132Sn, showing a consistent smooth reduction in SO energy for weakly bound orbits, attributed to extended radial wave functions rather than a reduced SO potential strength. These findings reinforce the need for further experimental research with advanced radioactive ion beam facilities to understand the intricate behaviors of SO interactions in exotic nuclei.